Authorship position as a proxy for contextual knowledge: a preliminary case study (Journal of EAHIL, 2023)
Current health sciences literature is predominantly disseminated by, through and for Western scholars, resulting in underrepresentation of contextual knowledge in health policies worldwide. Commonly, this literature is evidence-based, build on principles of universality, neglecting and disregarding the importance of contextual and local expertise. Using a global health research question applied to three countries, Maastricht University Library’s collection was evaluated to explore the extent of contextual knowledge by authorship positions. Preliminary results showed that while Dutch articles had more local authors on first and/or last authorship positions compared to Bangladesh and Tanzania, they had no Dutch authors in middle positions, as opposed to Bangladesh and Tanzania (23% and 16%).  This indicates a need for further understanding of geographic authorship position customs.Key words: Global health; Information dissemination; Information sources; Health information exchange; Diversity, Equity, Inclusion